Analisis Peran Stakeholder dalam Program Siak Hijau di Kabupaten Siak - M Subhan; Z Zulkarnaini; Geovani Meiwanda; Risky Arya Putri (Jurnal Ilmiah Wahana Pendidikan, 2022)
Success in natural resource management is highly dependent on the involvement of multi-stakeholders (stakeholders) to take part and work actively in efforts to achieve goals. Siak Regency is the only Regency that has been declared a Green Regency by the Minister of Environment and Forestry Siti Nurbaya. Siak Hijau through the Siak Hijau roadmap issued through the Decree of the Siak Regent Number 446/HK/KPTS/2020 which states that one of the action plans is the management of natural and environmentally sound natural resources which is one of the efforts of the Siak Regency government in managing natural resources in Siak Regency which is carried out by involving multiple parties. The research aims to reveal stakeholders, roles and relationships between stakeholders in environmental and sustainable natural resource management in accordance with the objectives of the Green Siak Program in Siak Regency. This study uses qualitative research methods with data collection techniques by observation, interviews and documentation. The results of the study indicate that there are 7 stakeholders identified as having an interest and influence in the management of natural resources and have carried out responsibilities in the implementation of the cooperation. These stakeholders are classified into key stakeholders, main stakeholders and supporting stakeholders. The relationship between stakeholders has a positive value, namely there is no potential conflict relationship, but there are still stakeholders who are not related to each other.